Interface‐Driven Partial Dislocation Formation in 2D Heterostructures. Issue 15 (20th February 2019) - Kim, Jung Hwa; Kim, Se‐Yang; Cho, Yeonchoo; Park, Hyo Ju; Shin, Hyeon‐Jin; Kwon, Soon‐Yong; Lee, Zonghoon
Abstract: Van der Waals (vdW) epitaxy allows the fabrication of various heterostructures with dramatically released lattice matching conditions. This study demonstrates interface‐driven stacking boundaries in WS2 using epitaxially grown tungsten disulfide (WS2 ) on wrinkled graphene. Graphene wrinkles function as highly reactive nucleation sites on WS2 epilayers; however, they impede lateral growth and induce additional stress in the epilayer due to anisotropic friction. Moreover, partial dislocation‐driven in‐plane strain facilitates out‐of‐plane buckling with a height of 1 nm to release in‐plane strain. Remarkably, in‐plane strain relaxation at partial dislocations restores the bandgap to that of monolayer WS2 due to reduced interlayer interaction. These findings clarify significant substrate morphology effects even in vdW epitaxy and are potentially useful for various applications involving modifying optical and electronic properties by manipulating extended 1D defects via substrate morphology control. Abstract : Extended 1D AB–AC stacking boundaries in WS2 are fabricated by using morphological defects on graphene substrates, such as graphene wrinkles. When the perfect basal dislocation direction is more perpendicular to the wrinkles, high‐density stacking boundaries are induced, due to the anisotropic friction of the wrinkles.